2016
DOI: 10.1364/oe.24.016309
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-independent and high-efficiency dielectric metasurfaces for visible light

Abstract: Artificial metasurfaces are capable of completely manipulating the phase, amplitude, and polarization of light with high spatial resolutions. The emerging design based on high-index and low-loss dielectrics has led to the realization of novel metasurfaces with high transmissions, but these devices usually operate at the limited bandwidth, and are sensitive to the incident polarization. Here, for the first time we report experimentally the polarization-independent and highefficiency dielectric metasurfaces span… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 50 publications
0
66
0
Order By: Relevance
“…Furthermore, it was reported that meta-atoms designed based on Huygens' principle with a multi-fold rotational symmetry had a polarization-independent response. The distortion induced by the mismatched lattices was also found to be very weak [65].…”
Section: Unangemeldetmentioning
confidence: 92%
“…Furthermore, it was reported that meta-atoms designed based on Huygens' principle with a multi-fold rotational symmetry had a polarization-independent response. The distortion induced by the mismatched lattices was also found to be very weak [65].…”
Section: Unangemeldetmentioning
confidence: 92%
“…The explosive field of metasurface has intrigued a huge interest from both physics and engineering communities due to its exotic behaviors and promising applications. It, composed of a mass of subwavelength‐spaced meta‐atoms, has afforded extraordinary capabilities to manipulate electromagnetic (EM) waves . The local amplitude, phase, and polarization are three important characteristics for output EM wavefront control, and previous pursuing of light manipulation via metasurfaces could be generally subjected into processing one or two of them.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, much attention has been paid to enhance the efficiency which is critically important for photonic devices. To date, different approaches were proposed to circumvent it in both reflection and transmission geometries, for example, by using active phase compensation, satisfying certain phase criterion, incorporating both electric and magnetic responses, low‐loss all‐dielectric metasurfaces, etc. However, these designs are confined to phase‐ or polarization‐only modulation, making the kaleidoscopic wavefront control particularly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a [0-2π] phase control has been achieved with tall cylinders (nanoposts) with high transmission [19][20][21][22]. In fact, the high diffraction efficiency provided by dielectric metasurfaces has been explored in many other classical applications, such as lenses [23][24][25], holograms [17][18][19]22,[26][27][28][29][30], wave plates [31], anomalous refraction generation [20,32], and vortex beam generation [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The choice of materials, as expected, plays an important role in the structures design. High index materials such as titanium dioxide (TiO 2 ) [25,29,34,35], silicon nitride (Si 3 N 4 ) [21], and silicon [17][18][19][20][26][27][28][30][31][32]36] are usually the preferred choice for this task. Silicon is particularly interesting for metasurface applications not only for its compatibility with CMOS processes, but also for its high refractive index that allows high-contrast gratings to be fabricated with low aspect ratio.…”
Section: Introductionmentioning
confidence: 99%